(untitled) (diségno, 2022)
Through the analysis of Luca Meda’s work, of which some sketches from his personal archive are presented, the contribution proposes a reflection on ‘design drawing’, focusing on the relationship between its two natures –one more technical and the other artistic– which in some cases interpenetrate harmoniously. The duality that was attributed to the industrial designer –a figure in the making in the 1950s– and the burden of having to harmonise ‘technical possibilities’ with ‘possibilities of form’, finds in Meda a successful synthesis in the use of manual drawing, an indispensable and effective tool both for technical design and for the poetic contextualisation of the object, almost a trait d’union between a concrete world, the one pertaining to technological aspects, and an abstract sphere, in relation to the symbolic values of objects and the emotional universe of the designer. Starting from Luca Meda’s multiple training –and bearing in mind the impact that new technological tools have on current design activity– the contribution identifies ‘design drawing’ as a real working methodology, still considered a foundation for the designer’s training. It is presented as relevant and inescapable precisely because of its ability to integrate two forms of knowledge, the technical and the artistic, often wrongly considered antagonistic.